(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Background: Budget planning is a cornerstone of organizational financial management, yet its systematic adoption remains uneven across transition economies.Objective: This study examines the theoretical underpinnings, methodological diversity, and practical application of budget planning with a focus on SMEs and vocational education institutions in Uzbekistan. Methods: A mixed-method approach combining structured literature review with descriptive field analysis of budgeting practices in the Andijan region.Results: Organizations adopting participatory, flexible, and technology-enabled budgeting systems demonstrate measurably stronger financial discipline and adaptive capacity under economic uncertainty. Key impediments include limited accounting infrastructure, skills deficits, and inadequate access to macroeconomic data.